Colorimetry of modified clays with mineral and organic additions - Martinez Molina, Wilfrido; Torres Acosta, Andres Antonio; Chavez Garcia, Hugo Luis; Alonso Guzman, Elia Mercedes; Lara Gomez, Cindy; Bedolla Arroyo, Juan Alberto; Lopez Calvo, Herwing Zeth; Ruvalcaba Sil, Jose Luis (Revista ALCONPAT, 2018)
The objective of this investigation was to quantify the colorimetric values of different clays with some additions. Exploring the aesthetic appreciation, based on the clay color, of different additions percentages (by clay mass) with Santiago Undameo Bank, Mexico, clays as main matrix. Clay was kaolinite and the additions were gypsum, lime, opuntia cactus mucilage, portland cement, and sodium hydroxide. The addition percentages were 2%, 4%, 6%, 8% and 10%. The best colorimetric performances were obtained from Portland cement at 6%, sodium hydroxide at 4%, lime and gypsum at 8% and opuntia cactus mucilage at 4% and 8%. Some buildings where these clay materials were used are: Casas grandes en Paquimé, Chihuahua, La Venta en Tabasco, Yácatas en Tzintzuntzan, among others.